Age interval and gender prediction using PARAFAC2 and SVMs based on visual and aural features - Pantraki, Evangelia; Kotropoulos, Constantine L.; Lanitis, Andreas (My University, 2017)
Parallel factor analysis 2 (PARAFAC2) is employed to reduce the dimensions of visual and aural features and provide ranking vectors. Subsequently, score level fusion is performed by applying a support vector machine (SVM) classifier to the ranking vectors derived by PARAFAC2 to make gender and age interval predictions. The aforementioned procedure is applied to the Trinity College Dublin Speaker Ageing database, which is supplemented with face images of the speakers and two single-modality benchmark datasets. Experimental results demonstrate the advantage of using combined aural and visual features for both prediction tasks.
Keywords: PARAFAC2; Automatic prediction; TCDSA database